Attitudes of Various Professional Groups towards the Use of Artificial Intelligence in the Migrant Recruitment Procedure - Grażyna Bartkowiak; Agnieszka Krugiełka (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu)
Aim: This article analyzes the attitudes of various professional groups toward using artificial intelligence (AI) in migrant recruitment. It includes a theoretical section discussing the need to employ migrants, the role of AI in recruitment, and the concept of attitudes as drivers of human behavior, as well as an empirical section presenting workshop-based research findings.